A suspensão do tempo na escultura de Rui Chafes - Quintela, Ana Carolina Marques da Cunha, 1991- (2016)
The work of Rui Chafes is the irreducible expression of a sculpturesque thinking that intends to overcome the limits of materiality, aiming the reencounter with a lost spirituality. From the various influences that his work welcomes, the spiritual legacy present in the late german gothic, the german romanticism, as well as the formal heritage of post-minimalism stand out. The objects build are only possible as the translation of an Idea, since, for the sculptor, the “matter is filthy and wrong”; denying their materiality, they’re solely the support of something which is before and after their own objectuality. Like so, by refusing them the matter, of which they are yet made of, and by providing, through the aesthetic experience, the spiritual transformation of the spectator, he irreversibly denies the time which resides in them, as a constituent of historical and chronological reality. Being time a fundamental dimension of the human existence, necessarily inherent to the artistic production, it seems suspended in the objects of Rui Chafes